Electrocardiograms in athletes: Interpretation and diagnostic accuracy - Lawless, C. E.; Best, T. M. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Electrocardiography (ECG) has been proposed as a method to enhance the ability of the preparticipation examination (PPE) to detect underlying cardiac conditions that can lead to sudden cardiac death (SCD) in young athletes.